2022
DOI: 10.1037/sgd0000460
|View full text |Cite
|
Sign up to set email alerts
|

Beyond diagnosis: “Gender dysphoria feels like a living hell, a nightmare one cannot ever wake up from”.

Abstract: Despite the central role of gender dysphoria in the lives of many transgender people, discussions of gender dysphoria remain scant in conversations about affirmative practice. As such, scholars have called for qualitative studies to explore gender dysphoria through the voices and perspectives of transgender people. The primary aim of this study is to use grounded theory methodology to gain a more in depth and comprehensive understanding of gender dysphoria from the perspectives of transgender adults. Data for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Furthermore, researchers have recently conceptualized gender dysphoria as a proximal minority stressor, finding that gender dysphoria is associated with anticipated social stigma and suggesting that experiences of gender dysphoria can involve the internalization of social experiences (Lindley & Galupo, 2020). Austin and colleagues (2021) call for more comprehensive, multidimensional conceptualizations of the impact and scope of experiences of gender dysphoria, but gender dysphoria associated with social contexts has not been quantitatively evaluated in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, researchers have recently conceptualized gender dysphoria as a proximal minority stressor, finding that gender dysphoria is associated with anticipated social stigma and suggesting that experiences of gender dysphoria can involve the internalization of social experiences (Lindley & Galupo, 2020). Austin and colleagues (2021) call for more comprehensive, multidimensional conceptualizations of the impact and scope of experiences of gender dysphoria, but gender dysphoria associated with social contexts has not been quantitatively evaluated in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, gender dysphoria is often defined as the distress that a transgender or nonbinary person may experience when their gender identity does not coincide with their sex or gender assigned at birth (American Psychological Association [APA], 2015). There is ample evidence that, for many, gender dysphoria is a powerful, internal experience that persists/exists even in affirming settings and after both social and medical transition have been achieved (Austin et al, 2021). However, prevailing, individual-focused conceptualizations of gender dysphoria as a personal disorder does not account for how factors outside of the individual (i.e., living in an oppressive and violent world) exacerbate experiences of gender dysphoria (Schulz, 2018).…”
Section: Gender Dysphoria and The Medical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender dysphoria is defined as emotional distress due to discrepancies between assigned sex and gender identity (Schneider et al, 2016). Gender dysphoria is a notable stressor for transgender folx (Austin et al, 2021; Galupo et al, 2019; Schneider et al, 2016), with links to suicidality, nonsuicidal self-injury, and body dissatisfaction (Peterson et al, 2017). This experience is particularly relevant for trans people, as few other identity groups must reconstruct their sense of self and, over time, internally manage misalignment between their assigned and true identities.…”
Section: Trans Minority Stress Theoretical Frameworkmentioning
confidence: 99%
“…Gender dysphoria has been described as a sense of incongruity between one's gender identity and that which was assigned at birth, and can occur on a social, emotional and/or personal level. 9,10 Gender dysphoria has been associated with extreme emotional distress for people and in a study by Austin et al, 11 one participant said that 'gender dysphoria feels like a living hell, a nightmare one cannot ever wake up from (p. 6). ' In regard to body dysmorphia, it has been reported that body dysmorphic disorder and some eating disorders share clinical traits and demonstrate high comorbidity.…”
Section: Introductionmentioning
confidence: 99%